Racial differences in family health history knowledge of type 2 diabetes: exploring the role of interpersonal mechanisms. Issue 4 (17th July 2018) - Lin, Jielu; Marcum, Christopher S; Myers, Melanie F; Koehly, Laura M
Abstract: Collecting complete and accurate family health history is critical to preventing type 2 diabetes. Whether there are any racial difference in family health history knowledge of type 2 diabetes and whether such differences are related to interpersonal mechanisms remain unclear. We seek to identify the interpersonal mechanisms that give rise to discrepancies in family health history knowledge of type 2 diabetes in families of different racial backgrounds. We analyze informant-dyad consensus with respect to shared family history of type 2 diabetes in 127 informants of 45 families in the greater Cincinnati area (white: 28 families, 78 informants; black/African-American: 17 families, 49 informants). We first document a difference in informant-dyad consensus by race and then test whether this difference can be explained by interpersonal ties, particularly health communication. Compared with their white counterparts, dyads in families of black/African-American background are more likely to have an uneven distribution of knowledge, with one informant knowing and the other not knowing his/her family health history. The racial difference is explained by dyads in families of black/African-American background having fewer reciprocal health communication ties. While associated with informant-dyad consensus, education, kinship ties, and closeness ties do not account for the observed racial difference. Activating health communication is a key to improving family health history knowledge, especially in families of black/African-American background. Researchers and clinicians should leverage communication ties in the family network for better collection and utilization of family health history in preventive services. Abstract : Racial differences in family health history knowledge are due to less health communication between family members of African American background.